Comparison of Activated Carbons Prepared from Indonesian Forest and Agricultural Residues - Hidayat, Arif; Rochmandi; Wijaya, Karna; Hinode, Hirofumi; Budiman, Arief (Asian Journal of Chemistry, 2012)
Activated carbons were prepared from biomass waste of bengkirai wood (Shorea laevifolia) and coconut shell using carbonization process. The carbonization temperature and carbonization holding time were tested in the ranges of 400-600 ºC for 2-6 h. The activated carbons resulted from this process were evaluated for BET surface area, pore size distribution and adsorption or iodine number. The results revealed that carbonization temperature and carbonization holding time gives significant effect on the pore structure of activated carbon produced. The highest BET surface area (271 m2/g) was obtained for coconut shell-activated carbon at the activation conditions of 800 ºC for 4 h.